Electrospray Ionization Linear Trap Quadrupole Orbitrap in Analysis of Old Tempera Paintings: Application to Nineteenth-Century Orthodox Icons. Issue 4 (August 2015) - Tripković, T.; Charvy, C.; Alves, S.; Lolić, A.Ð.; Baošić, R.M.; Nikolić-Mandić, S.D.; Tabet, J.C.
Proteomic approach in combination with mass spectrometry demonstrates a great potential for identification of proteinaceous materials in works of art. In this study we used a linear trap quadrupole Orbitrap (LTQ-Orbitrap), a state-of-the-art mass spectrometer for parts per million accuracy analyses of peptides behind tryptic hydrolysis. After the efficiency of the proteomic method was confirmed for reference and model samples, micro-samples from historical paintings were for the first time analysed using this technique. Superior performances of the liquid chromatography–mass spectrometry approach using a LTQ-Orbitrap mass spectrometer allowed identification of egg yolk peptides in two samples from nineteenth-century Orthodox icons, indicating egg tempera as the painting technique. Accurate precursor ion masses, in the range of ±2 ppm, and retention times of tryptic peptides strengthen protein identification. Additionally, in all historical samples the presence of animal glues suggested that the ground layer was likely bound using bovine collagen. Comparing to results acquired using matrix-assisted laser desorption/ionization time-of-flight tandem mass spectrometry in our previous study, here we achieved higher ion scores and protein scores, better sequence coverage and more identified proteins. In fact, a combination of the two mass spectrometric techniques provided overlapping and complementary data, related to the detection of peptides with different physicochemical properties.